To solve the expression 7x + y we can substitute x with 2 and y with 6.
= 7(2) + 6
= 14 + 6
= 20
Best of Luck!
solution:
Z1 = 5(cos25˚+isin25˚)
Z2 = 2(cos80˚+isin80˚)
Z1.Z2 = 5(cos25˚+isin25˚). 2(cos80˚+isin80˚)
Z1.Z2 = 10{(cos25˚cos80˚ + isin25˚cos80˚+i^2sin25˚sin80˚) }
Z1.Z2 =10{(cos25˚cos80˚- sin25˚sin80˚+ i(cos25˚sin80˚+sin25˚cos80˚))}
(i^2 = -1)
Cos(A+B) = cosAcosB – sinAsinB
Sin(A+B) = sinAcosB + cosAsinB
Z1.Z2 = 10(cos(25˚+80˚) +isin(25˚+80˚)
Z1.Z2 = 10(cos105˚+ isin105˚)
Answer:
x^2 ×1 2x + 36
Step-by-step explanation:
area of a square = L × B
= (x+6) (x+6) since a square has 4 equal sides, it becomes (x+6) (x+6)
= x(x+6) +6(x+6)
= x^2 + 6x + 6x +36
= x^2 + 12x +36 added all the like terms 6x + 6x = 12x
hope this helps ☆☆☆
Answer:
Step-by-step explanation:
<u>Mean of four numbers a, b, c, and d is 8:</u>
- (a + b + c + d)/4 = 8
- ⇒ a + b + c + d = 32
<u>Mean of seven numbers x, y, z, a, b, c and d is 12:</u>
- (x + y + z + a + b + c + d)/7 = 12
<u>Substitute the sum of 4 numbers:</u>
- x + y + z + 32 = 7*12
- x + y + z = 84 - 32
- x + y + z = 52
<u>Mean of x, y and z is:</u>
I don't know if this is right, but I'm pretty sure it's B.